2011
DOI: 10.1084/jem.20101459
|View full text |Cite
|
Sign up to set email alerts
|

The human syndrome of dendritic cell, monocyte, B and NK lymphoid deficiency

Abstract: Human immunodeficiency syndrome with loss of DCs, monocytes, and T reg cells; preservation of Langerhans cells; associated loss of BM multilymphoid progenitors; and overproduction of Flt3 ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
273
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(296 citation statements)
references
References 30 publications
14
273
3
6
Order By: Relevance
“…This could be due to a converted HSC signature or more likely to the loss of the Gata2-deficient HSCs in line with observations in haploinsufficient Gata2 mice 19 and with Gata2-deficient human BM showing a complete absence of the primitive CD38 -cells within the CD34 + progenitor compartment [43][44][45] . Even though we were limited to study progenitor-enriched Gata2-deficient cells we found these cells to exhibit a strong reduction of colony-forming ability and to be desensitized to TGFβ-induced growth arrest.…”
Section: Discussionsupporting
confidence: 80%
“…This could be due to a converted HSC signature or more likely to the loss of the Gata2-deficient HSCs in line with observations in haploinsufficient Gata2 mice 19 and with Gata2-deficient human BM showing a complete absence of the primitive CD38 -cells within the CD34 + progenitor compartment [43][44][45] . Even though we were limited to study progenitor-enriched Gata2-deficient cells we found these cells to exhibit a strong reduction of colony-forming ability and to be desensitized to TGFβ-induced growth arrest.…”
Section: Discussionsupporting
confidence: 80%
“…In the absence of DCs, the response induced by CD4 + T cells is impaired and bacterial load uncontrolled (36)(37)(38). Accordingly, individuals with a deficiency of DCs, monocytes, and B and natural killer (NK) cells (DCML deficiency) show increased susceptibility to poorly virulent strains of Mycobaterium spp (39). Similarly, mutations in the IFN regulatory factor 8, which have recently been shown to be associated with a selective loss of CD11c + CD1c + myeloid DCs, result in a remarkable increased susceptibility to disseminated bacillus Calmette-Guérin-osis, arguing for a specific role for DCs in resistance to mycobacteria (40).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple heterozygous germline mutations have been identified in GATA2 that are associated with a range of phenotypic presentations including MonoMAC [1][2][3] / dendritic cell, monocyte, B-and NK-lymphoid deficiency (DCML deficiency), [4][5] familial myelodysplastic syndrome/acute myelogenous leukemia (MDS/AML), 6 and lymphedema/Emberger syndrome. [7][8][9] The clinical presentation of the patient in the case report by Chu et al, 10 who had a history of M. avium complex (MAC) infection with cytopenias and was diagnosed with aplastic anemia and idiopathic CD4-positive (CD4 + ) lymphocytopenia (ICL), is not uncommon for MonoMAC patients.…”
mentioning
confidence: 99%